A STUDY ON FIGURATIVE LANGUAGE COVERING SIMILE, METAPHOR, PERSONIFICATION AND SYMBOL IN POEM - Raisa, Metha; Sudarsono, .; Rufinus, Albert (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to find out the students? ability to show figurative languages  and to mention their functions. The research was conducted to the Semester 3 students of English Education Study Program of Tanjungpura University in Academic Year 2016/2017. The research method used is descriptive study. The sample of this research consists of 70 students who are taking Poetry subject in Class A and Class B in Semester-3 of English Education Study Program. The technique of data collecting for this research is measurement test. From the calculation, the mean score of students? ability to show figurative language was 60,29. Therefore, the students? ability to show the expressions of figurative language is categorized as ?Average to Good?. From the computation, the students? mean score to mention the function of figurative language is 55,71, thus this result is categorized as ?Poor to Average?. The results of this study show that the students need more hours to learn about figurative language including the defintions, the functions, and the identification practice.Keywords: Figurative Language, Poem, Descriptive Study